The Role of Advocacy in Competition Policy : The Case of the Argentine Gasoline Market - Serebrisky, Tomas (World Bank, Washington, DC, 2014)
In 2000 the Argentine antitrust authorities conducted a study of the state of competition in the gasoline market. The study concludes with a set of policy recommendations (that is, limits to vertical integration and to the duration of contracts between oil companies and gasoline stations) which were subsequently implemented by the Argentine government. This was one of the rare occasions where the Argentine antitrust authorities exercised its advocacy role in a country that underwent an extensive process of deregulation and privatization. Serebrisky assesses the design and impact of the policies recommended by the Argentine antitrust authorities. In particular, he evaluates under which circumstances the new policies can reduce barriers to entry and foster competition in the Argentine gasoline market.